Government Policy on Retribution Services at the Traditional Bahari Market - Bakri La Suhu; Marno Wance; Abdul Halil Hi. Ibrahim; Darwin Abd Radjak (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to determine the Implementation of Ternate City Government Policy in Market Retribution Services at Bahari Berkesan Traditional Market, using a qualitative descriptive approach because the problems discussed in this study are not related to numbers, but describe, outline and depict situations and conditions in accordance with reality. Data collection techniques are carried out through observation, document interviews and secondary data assistance. while data collection techniques are carried out through observation, document interviews and secondary data assistance.The results of the study indicate that the Implementation of Ternate City Government Policy in Market Retribution Services at Bahari Berkesan Traditional Market is in accordance with the expected objectives, the parties involved in collecting market retribution, namely the Market Service as the person in charge of market management in Ternate City and the amount of retribution collected from retribution payers is in accordance with existing provisions, although sometimes the amount of retribution collected with tickets given to retribution payers (traders) does not comply with the rules. In addition, in the implementation of market retribution collection, especially in the Bahari Berkesan traditional market, there are four factors, namely communication, resources, disposition, and bureaucratic structure. However, in this study, the resource factor has a more sufficient influence to support the implementation of policies in collecting market retribution at the Bahari Berkesan Traditional Market. Policy Implementation; Government, Services; Market Retribution;